2020
DOI: 10.1111/jocn.15266
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of topical interventions to prevent or treat intravenous therapy‐related phlebitis: A systematic review

Abstract: Aims and objectives To evaluate the effectiveness of topical interventions in the prevention or treatment of intravenous therapy‐related phlebitis. Background Phlebitis is a severe inflammatory reaction that can be caused by intravenous therapy with hyperosmolar drugs. Although a variety of interventions are performed in several different countries, the most efficient method is yet to be established. Design A systematic review of randomised controlled trials (RCTs) was conducted. Methods Following the PRISMA c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 28 publications
1
16
0
7
Order By: Relevance
“…The tested products were calendula (Jourabloo et al, 2017), quercetin (Ghorbani et al, 2016), phellodendron (Wan, 2018), ichthammol glycerine (Basu et al, 2017;Thomas et al, 2016), sesame (Bigdeli Shamloo et al, 2019;Damanik, 2017) and chamomile (Lila, 2017). The results reported on the benefits of phytotherapeutic products concur with those of other studies and systematic reviews (Dos Reis et al, 2009;Gao et al, 2016;Goulart et al, 2020;Martín Gil et al, 2017). The efficacy of these products is due to their anti-inflammatory, anti-oxidant, anti-oedematous, anti-pyretic and anti-nociceptive properties (Bigdeli Shamloo et al, 2019).…”
Section: Products Used and Their Efficacysupporting
confidence: 88%
See 2 more Smart Citations
“…The tested products were calendula (Jourabloo et al, 2017), quercetin (Ghorbani et al, 2016), phellodendron (Wan, 2018), ichthammol glycerine (Basu et al, 2017;Thomas et al, 2016), sesame (Bigdeli Shamloo et al, 2019;Damanik, 2017) and chamomile (Lila, 2017). The results reported on the benefits of phytotherapeutic products concur with those of other studies and systematic reviews (Dos Reis et al, 2009;Gao et al, 2016;Goulart et al, 2020;Martín Gil et al, 2017). The efficacy of these products is due to their anti-inflammatory, anti-oxidant, anti-oedematous, anti-pyretic and anti-nociceptive properties (Bigdeli Shamloo et al, 2019).…”
Section: Products Used and Their Efficacysupporting
confidence: 88%
“…Systemic and topical treatments are available, with the latter the most commonly used to control symptoms and alleviate patient discomfort (Di Nisio et al, 2015; Lian et al, 2017). However, there is a lack of consensus on topical interventions, with only two systematic reviews conducted on this topic (Goulart et al, 2020; Martín Gil et al, 2017). The study by Martín Gil et al (2017) reported on the pharmacological (heparinoids, diclofenac, nitroglycerine) and phytotherapeutic products (chamomile, notoginseny, aloe vera) used in the treatment of phlebitis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, there is a divergence in the literature and scarcity on the subject so commonly used in clinical practice by nursing. Although effective, the compresses are insufficient to treat phlebitis alone, requiring their association with herbal medicines or other therapeutic modalities, to reduce the risk of progression to thromboembolism (BARBOSA et al, 2016;WELYCZKO, 2020;GOULART et al, 2020;ZHENG et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Phlebitis is a local complication of peripheral intravenous (IV) therapy, a technical-scientific process performed by the nursing team, which consists of the insertion of a peripheral venous catheter (PIVIC). Its classification is mostly ordered by visual scales, with Visual Infusion Phlebitis (VIP) being the most commonly used (MILUTINOVIC et al, 2015;GOULART et al, 2020).…”
Section: Introductionmentioning
confidence: 99%